Interaktif dalam Pembelajaran IPS - Yulia Tri Samiha (JIP Jurnal Ilmiah PGMI, 2017)
Interactive learning is often known as the child's question approach. This model is designed so that students will ask questions and then find answers to their own questions. Stages in the interactive learning model consist of early knowledge preparation, exploration activities, student questions, inquiry, final knowledge and reflection. Teachers in this interactive learning process can develop effective inquiring techniques or engage in creative dialogue by asking questions to students. The nature of the question can reveal something or have inquiry properties, so through the questions asked, students are developed in their ability to think creatively of facing event.